Temporal trends in the incidence of adverse effects of medical treatment in BRICS countries from 1990 to 2021: an age-period cohort analysis - Wei, Xingmin; Jiang, Lu; Zhang, Zhidong; Shang, Longjian; Liu, Kun; Qin, Xiaoang; Ding, Gaoheng; Liu, Lu; Wu, Jianjun (Frontiers in Public Health, 2025)
BackgroundSignificant disability-adjusted life year (DALY) losses are caused annually by adverse effects of medical treatment (AEMT), a serious public health concern worldwide that continuously strains nations’ socioeconomic progress. As they account for more than half of the world’s population and exhibit notable variation in healthcare resource distribution, the BRICS nations—Brazil, Russia, India, China, and South Africa—have emerged as a crucial observational cohort for researching healthcare safety issues. This study evaluated trends in the incidence of AEMT across BRICS nations from 1990 to 2021.MethodsThis study evaluated trends in the incidence of AEMT in the BRICS nations between 1990 and 2021, utilizing data from the Global Burden of Disease (GBD) 2021 database. We employed Joinpoint regression to determine the average annual percentage change (AAPC) in incidence. Additionally, net drift, localized drift, age-specific curves, and period/cohort relative risk were estimated through an age-period-cohort (APC) model implementing the intrinsic estimator (IE) algorithm.ResultsBetween 1990 and 2021, the incidence of AEMT decreased in both South Africa and China. Notably, China exhibited a more pronounced decline, with an AAPC of −1.30% (from 36.94 per 100,000 to 24.65 per 100,000), compared to South Africa’s AAPC of −0.98% (from 117.82 per 100,000 to 86.57 per 100,000). In contrast, Brazil and Russia showed upward trends. Brazil experienced the most substantial increase, rising from 23.06 per 100,000 to 75.09 per 100,000 (AAPC +3.88%), while Russia’s incidence grew less markedly, from 153.97 to 188.67 cases per 100,000 (AAPC +0.65%). Notably, China exhibited a consistently lower incidence of AEMT compared to other BRICS nations. The burden of AEMT disproportionately affected the older adult population in Brazil, South Africa, India, and Russia, whereas in China, the highest incidence was observed among newborns and young children. Regarding cohort risk, all nations demonstrated a reduction over time, except for Brazil and Russia, where cohort relative risk increased significantly.ConclusionOver the past three decades, divergent trends in AEMT incidence have been observed across the BRICS nations. To strengthen AEMT prevention, these countries should prioritize optimizing existing healthcare resources, such as workforce training and surveillance systems. Additionally, targeted interventions—including enhanced care for vulnerable populations (e.g., young children, preschoolers, and the older adult)—are critical to further reducing AEMT incidence.